1997
DOI: 10.1161/01.atv.17.10.1995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bone Marrow Transplantation on Lipoprotein Metabolism and Atherosclerosis in LDL Receptor–Knockout Mice

Abstract: The LDL receptor (LDLR) plays an important role in the removal of LDL and its precursors, the intermediate and very low density lipoproteins, from the blood circulation. The receptor is expressed on various cell types. In this study the relative importance of the LDLR on macrophages for lipoprotein metabolism and atherogenesis was assessed. For this purpose, irradiated LDLR-knockout (-/-) mice were transplanted with bone marrow of normal C57BL/6J mice. DNA analysis showed that the transplanted mice were chimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…Second, LDLr expression in the vascular wall does not affect atherogenesis ( 27 ). Therefore, our data strongly suggest that whether LDL is more proatherogenic than VLDL is dependent on the topographic site.…”
Section: Differences Of the Histological Composition Of Atherosclerotmentioning
confidence: 64%
“…Second, LDLr expression in the vascular wall does not affect atherogenesis ( 27 ). Therefore, our data strongly suggest that whether LDL is more proatherogenic than VLDL is dependent on the topographic site.…”
Section: Differences Of the Histological Composition Of Atherosclerotmentioning
confidence: 64%
“…We previously demonstrated that transplantation of C57Bl/6 bone marrow into LDLr(Ϫ/Ϫ) mice, which had serum cholesterol levels 9-fold higher than those of the mice in the present study even without cholate added to the diet, did not result in an increase of the atherosclerotic lesion area. 13 Although different animal models were used to analyze diet-induced (with and without the addition of cholate) atherosclerosis in these studies, which could make direct comparisons difficult, the present data strongly suggest that the LDLr can facilitate foam cell formation only under conditions of moderate cholesterol levels. Analysis of LDLr expression in more advanced foam cell-rich lesions of control transplanted C57Bl/63 C57Bl/6 mice revealed that in these mice, the macrophage LDLr is downregulated during the progression of lesion development.…”
Section: Discussionmentioning
confidence: 79%
“…Previously, we showed that the method of BMT in mice results in an almost complete replacement of recipient hemopoietic cells by those of donor origin. 13 During the weeks after BMT, the total serum cholesterol level was repeatedly determined. No significant differences between LDLr(Ϫ/Ϫ)3 C57Bl/6 and C57Bl/63 C57Bl/6 could be observed at 4 and 8 weeks after BMT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations